UPAYA PENINGKATAN KINERJA ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA UNIT KEAMANAN DAN KESELAMATAN DALAM MENCEGAH PELANGGARAN LALU LINTAS DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA MAGELANG (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The aim of this research is to identify the causes of the sub-optimal performance of members of the South Kalimantan Police Unit in preventing traffic violations in the jurisdiction of the Magelang Police and to formulate efforts to improve the performance of members of the South Kalimantan Police Unit in preventing traffic violations in the jurisdiction of the Magelang Police. Efforts to improve the performance of South Kalimantan Police Unit members in preventing traffic violations in the jurisdiction of the Magelang Police are through 3 actions, namely (a) Preemptive actions implemented include socialization of Traffic Regulations within the Magelang Education Service, Children's Friend Police Program, Traffic Safety Campaign , Mou With Partners; (b) Preventive actions such as Safety Reading activities, implementation of the Bureaucratic Reform Program within the Magelang Police Traffic Unit regarding cooperation in traffic accident prevention programs, Operation Simpatik Candi and various other activities including: carrying out personnel deployments during accident-prone hours, implementing Check Points and traffic complaints to road users; (c) Repressive measures with law enforcement, such as Temple Safety Operations, taking action against overloading violations, taking action against modified vehicles and protocols that are not roadworthy.
Keywords: Performance; Police; Prevention; Traffic Violations